Highly Efficient Simple-Structure Sky-Blue Organic Light-Emitting Diode Using a Bicarbazole/Cyanopyridine Bipolar Host - Li, Deli; Li, Jiuyan; Liu, Di; Li, Wei; Ko, Chang-Lun; Hung, Wen-Yi; Duan, Chunhui (ACS applied materials & interfaces, 2021)
Up to now, the most efficient blue phosphorescent organic light-emitting diode (PhOLED) was achieved with a maximum external quantum efficiency (ηext) of 34.1% by using an exciplex cohost. It still remains a challenge to obtain such high efficiencies using a single-host matrix. In this work, a highly efficient sky-blue PhOLED is successfully fabricated using a newly developed bipolar host material, namely 5-(2-(9H-[3,9′-bicarbazol]-9-yl)phenyl)nicotinonitrile (o-PyCNBCz), which realizes a ηext of 29.4% at a practical luminance of 100 cd m–2 and a maximum ηext of 34.6% (at 23 cd m–2). The present device is characterized by simple configuration with a single host and single emitting layer. o-PyCNBCz also reveals high efficiency of 28.2% (94.8 cd A–1) when used as the host for green PhOLED. Under identical conditions, o-PyCNBCz always outperforms than its isomer 3-PyCNBCz (5-(9-phenyl-9H-[3,9′-bicarbazol]-6-yl)nicotinonitrile) in terms of more balanced charge transportation, higher photoluminescent quantum yields of over 90%, and higher horizontal orientation ratio of the emitting dipole for the host-dopant films, which finally lead to its superior performance in PhOLEDs. It is observed that all these merits of o-PyCNBCz benefit from its ortho-linking style of carbazole (p-type unit) and cyanopyridine (n-type unit) on the phenylene bridge and the resultant molecular conformation.